Are serum and biliary carcinoembryonic antigen and carbohydrate antigen19-9 determinations reliable for differentiation between benign and malignant biliary disease? - Meral AKDOĞAN,; Erkan PARLAK,; Burçak KAYHAN,; Mevhibe BALK,; Gül ERSAVAŞTF,; Burhan ŞAHİN, (Turkish Journal of Gastroenterology, 2019)
-